9-O-butyl-13-(4-isopropylbenzyl)berberine, KR-72, Is a Potent Antifungal Agent That Inhibits the Growth of Cryptococcus neoformans by Regulating Gene Expression - Bang, Soohyun; Kwon, Hyojeong; Hwang, Hyun Sook; Park, Ki Duk; Kim, Sung Uk; Bahn, Yong-Sun (PUBLIC LIBRARY SCIENCE, 2014)
In this study we explored the mode of action of KR-72, a 9-O-butyl-13-(4-sopropylbenzyl)berberine derivative previously shown to exhibit potent antifungal activity against a variety of human fLingal pathogens. The DNA microarray data revealed that KR-72 treatment significantly changed the transcription profiles of C. neoformans, affecting the expression of more than 2,000 genes. Genes involved in translation and transcription were mostly upregulated, whereas those involved in the cytoskeleton, intracellular trafficking, and lipid metabolism were dovvnregulated. KR-72 also exhibited a strong synergistic effect with the antifungal agent FK506. KR-72 treatment regulated the expression of several essential genes, including ECM16, NOP14, HSP10 and MGE1 which are required for C. neoformans growth. The KR-72-mediated induction of MGE1 also likely reduced the viability of C. neaformans by impairing cell cycle or the DNA repair system. In conclusion, KR-72 showed antifungal activity by modulating diverse biological processes throLigh a mode of action distinct from those of clinically available antifLingal drugs such as polyene and azole drugs
Keywords: NUCLEOTIDE EXCHANGE FACTOR; OXYSTEROL-BINDING PROTEIN; MITOCHONDRIAL HSP70; YEAST HOMOLOG; GRPE; OVEREXPRESSION; CHAPERONIN-10; FLUCONAZOLE; RESISTANCE; BERBERINE